Sex differences in atrial remodeling and its relationship with myocardial fibrosis in hypertrophic obstructive cardiomyopathy - Bi, Xuanye; Song, Yanyan; Yang, Chengzhi; Song, Yunhu; Zhao, Shihua; Qiao, Shubin; Zhang, Jinying (Frontiers in Cardiovascular Medicine, 2022)
Background: To explore the effect of sex on left atrial (LA) remodeling and its relationship with myocardial fibrosis in patients with obstructive hypertrophic cardiomyopathy(HOCM). Methods and Results: Eighty-five patients with HOCM were enrolled. Myocardial fibrosis was quantified by the collagen volume fraction(CVF) in myocardial samples. Early atrial peak of emptying rate(PER-E) was assessed by LA volume/time(V/t) curves derived from cardiac magnetic resonance imaging (CMR) analysis. PER-E index was PER-E normalized by left ventricular filling volume. HOCM patients showed lower PER-E index than healthy controls(P=0.027). Compared with males, the PER-E (P<0.001) and PER-E index(P=0.012) in females were lower. In CVF- stratified subgroups, sex difference in PER-E index was eliminated (P>0.05). The CVF was correlated with PER-E and PER-E index in both sexes (all P<0.05). In multivariate regression analysis, sex(P=0.007) and CVF(P<0.001) were independently correlated with PER-E(all P<0.05). Conclusions: HOCM patients presented LA reverse remodeling. Impaired LA function was more common in female patients with HOCM due to their susceptibility to myocardial fibrosis.